Characterization and comparative analysis of the genome of Puccinia sorghi Schwein, the causal agent of maize common rust - Rochi, Lucía; Dieguez, Maria Jose; Burguener, Germán; Darino, Martín Alejandro; Pergolesi, María Fernanda; Ingala, Lorena Romina; Cuyeu, Alba Romina; Turjanski, Adrián; Kreff, Enrique D.; Sacco, Francisco (Elsevier, 2018)
Rust fungi are one of the most devastating pathogens of crop plants. The biotrophic fungus Puccinia sorghi Schwein (Ps) is responsible for maize common rust, an endemic disease of maize (Zea mays L.) in Argentina that causes significant yield losses in corn production. In spite of this, the Ps genomic sequence was not available. We used Illumina sequencing to rapidly produce the 99.6 Mb draft genome sequence of Ps race RO10H11247, derived from a single-uredinial isolate from infected maize leaves collected in the Argentine Corn Belt Region during 2010. High quality reads were obtained from 200 bp paired-end and 5000 bp mate-paired libraries and assembled in 15,722 scaffolds. A pipeline which combined an ab initio program with homology-based models and homology to in planta enriched ESTs from four cereal pathogenic fungus (the three sequenced wheat rusts and Ustilago maydis) was used to identify 21,087 putative coding sequences, of which 1599 might be part of the Ps RO10H11247 secretome. Among the 458 highly conserved protein families from the euKaryotic Orthologous Groups (KOG) that occur in a wide range of eukaryotic organisms, 97.5% have at least one member with high homology in the Ps assembly (TBlastN, E-value ⩽ e−10) covering more than 50% of the length of the KOG protein. Comparative studies with the three sequenced wheat rust fungus, and microsynteny analysis involving Puccinia striiformis f. sp. tritici (Pst, wheat stripe rust fungus), support the quality achieved. The results presented here show the effectiveness of the Illumina strategy for sequencing dikaryotic genomes of non-model organisms and provides reliable DNA sequence information for genomic studies, including pathogenic mechanisms of this maize fungus and molecular marker design.